The role of trichoscope in diagnosing scalp psoriasis and seborrheic dermatitis - Van, Pham Dao Tuong; Nhung, Ly Thi My (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Objective: To characterize the trichoscopic features of scalp psoriasis and seborrheic dermatitis and to evaluate the diagnostic value of trichoscopy in differentiating these two conditions. Methods: A descriptive case series was conducted at Ho Chi Minh City Hospital of Dermatology from March to August 2024. Eighty-seven adult patients clinically diagnosed with scalp psoriasis (n = 50) or seborrheic dermatitis (n = 37) were enrolled. Trichoscopic examination of representative lesions was performed using a Handyscope® device at ×10 magnification. Vascular distribution, vessel morphology, erythema, and scale color were systematically recorded. The diagnostic performance of selected trichoscopic features was assessed using sensitivity, specificity, positive predictive value, and negative predictive value. Results: Dotted vessels were observed in 84.0% of psoriasis cases and were absent in seborrheic dermatitis, showing 84.0% sensitivity and 100.0% specificity for psoriasis. Uniformly distributed vessels were also predominant in psoriasis (92.0% vs 18.9%). In contrast, arborizing vessels and non-uniform vascular distribution were more common in seborrheic dermatitis. White or silvery scales were more frequently observed in psoriasis, whereas yellow greasy scales appeared exclusively in seborrheic dermatitis, with 100.0% specificity for that diagnosis. Conclusion: Trichoscopy is a useful non-invasive tool for differentiating scalp psoriasis from seborrheic dermatitis by identifying characteristic vascular and scaling patterns. Its routine use may improve diagnostic accuracy in clinical dermatology practice.